Outcome of patients with previous coronary artery bypass grafting and severe calcific aortic stenosis receiving transfemoral transcatheter aortic valve replacement. Issue 2 (12th November 2019) - Höllriegel, Robert; Spindler, Aileen; Kiefer, Philipp; Woitek, Felix J.; Leontyev, Sergey; Haussig, Stephan; Crusius, Lisa; Stachel, Georg; Schlotter, Florian; Hommel, Jennifer; Borger, Michael A.; Thiele, Holger; et al.
Abstract: Objectives: To evaluate the impact of previous coronary artery bypass grafting (CABG) on early safety at 30 days and 1‐year mortality in patients receiving transcatheter aortic valve replacement (TAVR). Background: The use of TAVR in patients with previous CABG suffering from severe aortic stenosis has increased in the last years. Methods: Consecutive TAVR patients were stratified according to previous CABG versus no previous cardiac surgery (control). All‐cause 1‐year mortality and early safety at 30 days were evaluated. Results: In the unmatched cohort and compared to control ( n = 2, 364), CABG ( n = 260) were younger, more often male and suffered more often from comorbidities leading to an increased STS‐score ( p < .001). The rate of early safety events at 30 days was comparable between CABG and control (21.2% vs. 24.6%, p = .22) with a higher mortality in CABG (9.6% vs. 5.3%, p = .005). All‐cause 1‐year mortality was higher in CABG compared to controls (HR 1.51 [95%‐CI 1.15–1.97], p = .003). Applying Cox regression analysis, both 30‐day (HR 1.57 [95%‐CI 0.97–2.53], p = .067) and all‐cause 1‐year mortality (HR 1.24 [95%‐CI 0.91–1.70], p = .174) were not significantly different between groups. After propensity‐score matching, the rate of early safety events at 30 days was lower in CABG compared to controls (21.6% vs. 31.7%, p = .02). Thirty‐day (9.1% vs. 7.7%, p = .596) and all‐cause 1‐year mortality (24.0% vs. 23.1%, p = .520, HR 1.14 [95%‐CI 0.77–1.69], p = .520) were not different between groups. Conclusion: In patients receiving TAVR, previous CABG was not associated with an increase in periprocedural complications and all‐cause 1‐year mortality when adjusted for other comorbidities.